Predicting 10-year Cardiovascular Risk Using WHO/ISH Risk Prediction Chart among Rural Population in Haryana, India - Pooja Jaswal; Pabalpreet Kaur; Jyoti Sarin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: CVD are leading cause of premature Deaths worldwide. Coronary vascular disease (CVD)risk estimation tools are a simple means of early identifying those at high risk in a community. It seems to bea cost-effective strategy for CVD prevention in developing countries. The WHO /ISH risk prediction chartsestimates risk of people having CVD’s for next ten years, who do not develop coronary heart disease orstroke. Methods: A total of 100 subjects between 40 to 70 years of age were included in this cross sectionalstudy. Total 100 families were visited and subjects were selected randomly. CVD risk was calculated byasking information from the subjects regarding Age, gender, smoking status, measuring their blood pressure,history of diabetes. The chart classifies an individual into different risk of having CVD’S that categorizedinto low (<10%), moderate (10% to <20%), high (20% to <30%), and very high (>30%) risk groups. Results:Less than two-third (62%) of population has less than 10% CVD risk, followed by less than one-third (31%)of the population had CVD risk of between 10- to <20% for the next 10 years. Only 6 subjects had 20-<30%of risk followed by 1% CVD risk between 30-<40%.Age, More SBP, Abdominal obesity, smoking, diabetesmellitus and More BMI (p<0.0001) were significantly associated with higher CVD risk. Conclusions:WHO/ISH Chart should be used by peripheral health workers for early identification of people with a highrisk for CVD and provide timely services in reducing the complications and premature deaths related toCVD in India.